Mindfulness-based interventions and their relationships with body image and eating behavior in adolescents: a scoping review - Silvia Patrícia de Oliveira Silva Bacalhau; Luciana Gonçalves de Orange; Marco Aurélio de Valois Correia Junior; Juliana Vieira Nunes; Carolina Larissa Alves Sales de Almeida; Maria Wanderleya de Lavor Coriolano-Marinus (Journal of Eating Disorders)
Abstract Background During adolescence, there are risks of changes in eating behavior and concerns about weight and body shape. Mindfulness-based interventions (MBIs) may bring benefits to this population. Objective This study aimed to assess research that carried out MBIs and its repercussions onbody image and eating behavior in non-clinical adolescents. Methods This is a scoping review study that followed the JBI methodology and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) protocol, and was registered in the Open Science Framework ( https://doi.org/10.17605/OSF.IO/3VB6K ). An initial search in MEDLINE (PubMed) was performed, followed by analysis of the words contained in the titles, abstracts and indexed terms. The identified keywords and indexed terms (“adolescent”, “body image”, “feeding behavior”, “mindfulness”, “mindful eating”, “body dissatisfaction” and “body dysmorphic disorders”) were used for research in PubMed, Web of Science, Embase and Scopus. There was no language restriction and the selection considered articles published up to December 2023. Duplicate articles were removed and, after analyzing the title, abstract and keywords, the selected articles were read in full, excluding those that did not meet the proposed eligibility criteria. The references of the initially selected articles were researched in additional sources. Results Six studies out of a total of 665 were found. Five studies were randomized controlled trials and one was a single-arm pilot study. Of the six studies, three found positive relationships between MBIs and eating behavior (increased awareness of eating behaviors, significant reductions in dietary restraint and eating disorder symptoms) and/or body image (reduced concerns about weight and body shape, as well as negative affect - through improved emotional regulation). Three studies did not find statistically significant results. Conclusion MBIs appear to improve eating behavior and body image acceptance; however, further research is needed to draw more robust conclusions. Heterogeneity among the methodologies used was observed: variations in sample sizes, age groups and gender of participants, and protocols used, which prevents generalization of the results to adolescents and corroborates the need to create a protocol based on information already available in the literature.